Pendampingan Legalitas Masjid Melalui Sertifikasi Tanah Wakaf Dalam Rangka Perlindungan Aset Keagamaan di Desa Simbarwaringin, Kec. Trimurjo, Kab. Lampung Tengah - Ismail, Habib; Arsyad, Mufid; Rahmawati, Rita; Anjas, Muhammad; Seftina, Any Shifa (Al-Khidmah Jurnal Pengabdian Masyarakat, 2025)
The main problem faced by Darussalam Mosque in Simbarwaringin Village, Trimurjo District, Central Lampung Regency, is the absence of a waqf land certificate since the mosque was established in 1980. This condition has caused legal uncertainty, potential disputes, and weak protection of religious assets. The obstacles include the lack of official waqf documentation, limited understanding of mosque administrators regarding legalization procedures, and conflicts in asset management, such as the kindergarten (TK) building on waqf land with non-transparent management. The purpose of this assistance activity is to provide understanding to the community and mosque administrators about the importance of waqf legalization, strengthen the nazhir institution, and accelerate the certification process of waqf land in order to obtain clear legal protection. The method used is the Asset-Based Community Development (ABCD) approach by positioning Darussalam Mosque as the main asset. The assistance was carried out through socialization of waqf regulations, legal education, facilitation of community deliberations, tracing the origin of the waqif, preparation of supporting documents, and coordination with the Waqf Pledge Deed Official (PPAIW), Religious Affairs Office (KUA), and the National Land Agency (BPN). The results of the assistance showed an increase in the community’s legal awareness, the formation of an official nazhir body consisting of at least five members, and the strengthening of mosque institutional governance. In addition, the legalization process opened opportunities to restore the management of waqf assets that had previously lacked transparency so that they return under nazhir’s control. Thus, waqf certification not only provides legal certainty over mosque land but also promotes the empowerment of mosque institutions as centers of worship, social activities, and education in Simbarwaringin Village.